If root(x+iy) = plus or minus(a+ib), then root(-x-iy) is equal to (1) plus or minus(b+ia) (2)plus or minus(a-ib) (3) (ai+b) (4) plus or minus(b-ia) (5) None of these

Solution:

Given √(x+iy) = ±(a+ib)

Squaring both sides

(x+iy) = (a+ib)2

= a2+2aib-b2

= a2-b2+2aib

Comparing real and imaginary part

x = a2-b2

y = 2ab

-x-iy = -a2+b2-i2ab

= (-b+ia)2

Taking square root

√(-x-iy) = ±(-b+ia)

Hence option (5) is the answer.

Was this answer helpful?

 
   

3 (6)

(10)
(3)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

Ask
Question